(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Advanced sustainable materials with high performance are garnering a lot of attention nowadays due to rising environmental concerns. Natural fiber reinforced polymer (NFRP) composites are currently one of the huge demands to replace conventional materials as it inhibits great properties, low cost, abundantly available, and environmentally friendly. There are various ways to fabricate NFRP composites such as compression molding, resin transfer molding, etc. However, these methods have several disadvantages (e.g., non-uniform temperature distribution, longer processing time, and high cost). This paper reviews the current trend of utilizing microwave curing in fabricating NFRP as it provides volumetric heating, less power consumption, and is more efficient.